Analysis of Digital Evidence on Denial of Service (DoS) Attack Log Based - Galih Fanani; Imam Riadi (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
This research is carried out an analysis and investigation of digital log file data retrieval from DoS (Denial of Service) attacks, on internet networks that have been detected by IDS (Intrusion Detection System) and using Wireshark as Tools Analysis Network. The research phase begins with the design of an experimental scenario which is often carried out daily where users access the internet network. The next stage is an attack in the form of a ping flood on the target computer connected to the internet network, the final stage of data retrieval which will be analyzed later. Testing research using UAT (User Acceptance Test), to prove that the analysis has been received by the user. The results of research conducted to obtain data in the form of an attacker's IP (Internet Protocol), target IP, protocol type, the port used, and the time of the attack. In the UAT test results, the obtained value of 18% of students disagrees, 58% of students agree, and 24% of students strongly agree. This research has conducted an analysis of random data attacks using Wireshark applications received by users.